PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DI BURSA EFEK INDONESIA - Rennia Sofi Dia Anugra Heni; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTMaximizing enterprise value is one of the company's goals that can be achieved through the financial management functions. In this case, one financial decision will influence other financial decisions and have an impact on the enterprise value.  This study aims to measure the impact of investment decisions, funding decisions and dividend policies on property companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2018 with the selection of samples using purposive sampling technique. Based on several tests on 57 samples obtained, by using normality test, autocorrelation test, heteroskidasticity test and multiple linear regression test, concluded that investment decisions and funding decisions have a significant positive effect on the enterprise value. While the dividend policy has a negative effect that is not significant on the enterprise value.